STUDY OF ZIRCONIUM ADDITION AND HEAT TREATMENT ON MICROSTRUCTURE, MARTENSITIC TRANSFORMATION BEHAVIOR, AND CORROSION RESISTANCE OF SHAPE MEMORY ALLOY NITINOL Ti-Ni-Mo-Fe - Setyabudi, Ryan
Heart disease is the leading cause of death globally. One method of treatment for coronary heart disease is the installation of stents, which is form of arterial supporting pipes to facilitate blood flow. Most of the stents developed are based on nitinol (NiTi) alloys. To improve the performance and biocompatibility of nitinol stents, such as shape memory effect, martensitic transformation temperature, and corrosion resistance, the addition of alloying element and heat treatment needs to be done. This present study will add a certain amount of Zr and perform heat treatment to Ti50Ni49.5Mo0.3Fe0.2 alloy to study its effect on the microstructure, martensitic transformation behavior and corrosion resistance of the alloy. A series of experiments were conducted to study zirconium addition and heat treatment on microstructure, martensitic transformation behavior, and corrosion resistance of shape memory alloy nitinol. The research begins with the melting of alloy elements in the form of nickel ball bearings (> 99.8%), titanium rod (> 99%), molybdenum rod (99.9%), iron chips (99.98%), zirconium sponge foam (99.9%) using direct current electric arc furnace followed by homogenization of the alloy using horizontal tube furnaces in an inert environment. Furthermore, some alloys were heat treated at a temperature of 8500C for one hour using horizontal tube furnace in an inert environment. The alloys were then prepared and immersion tested in a physiological solution of 0.9% NaCl for 14 days at 37 ± 0.50C. Subsequently, the alloys were characterized using optical microscopy, x-ray diffraction, scanning electron microscope-energy dispersive spectroscopy, and differential scanning calorimetry. Based on the research conducted, variations in the addition of Zr elements (0,1,2,3 at.%) resulted formation of austenite B2 phase, B19 ’martensite, R-phase, and Ti2Ni. Immersion testing results showed that addition of Zr (3 at.%) and heat treatment produced the best corrosion resistance with a corrosion rate of 0.007134 mmpy. While alloys with heat treatment showed a decrease in corrosion resistance with the greatest corrosion rate of 0.020077 mmpy. In addition, the results of the measurement of martensitic transformation temperature added Zr (3 at.%) without heat treatment showed the highest value of 284.90C (Ms) and 103.90C (Mf), while the heat treatment tended to decrease the martensitic transformation temperature.